The Role of the Cephalopod Digestive Gland in the Storage and Detoxification of Marine Pollutants - Rodrigo, Ana P. (2018)
COST Action FA1301 "A network for improvement of cephalopod welfare and husbandry in research, aquaculture and fisheries (CephsInAction)" The Portuguese Foundation for Science and Technology (FCT) MARE through the strategic programme (UID/MAR/04292/2013; SFRH/BD/109462/2015; IF/00265/2015) GreenTech (PTDC/MARBIO/0113/2014) FCT